2018
DOI: 10.1136/heartjnl-2018-313802
|View full text |Cite
|
Sign up to set email alerts
|

Familial clustering of bicuspid aortic valve and its relationship with aortic dilation in first-degree relatives

Abstract: ObjectiveBicuspid aortic valve (BAV) is the most common congenital heart disease. This study aimed to determine the prevalence rate of BAV in first-degree relatives (FDR) and the inheritance pattern according to different morphotypes and aortic dilation.MethodsBAV probands were consecutively studied at eight tertiary referral centres. After sequential screening, FDR were included in the study. The BAV morphotype, aortic dilation and aortic phenotype were assessed by transthoracic echocardiography.ResultsSeven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
51
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 30 publications
3
51
2
Order By: Relevance
“…In this issue of Heart , Galian-Gay et al 1 found a BAV on echocardiographic screening in 6.5% of 724 first-degree relatives of 256 BAV patients, consistent with significant heritability although valve morphology was not concordant within families. In addition, 9.6% of relatives with a trileaflet valve were found to have aortic dilation, defined as 1.96 SD greater than expected for age, body size and sex (figure 1).…”
mentioning
confidence: 87%
“…In this issue of Heart , Galian-Gay et al 1 found a BAV on echocardiographic screening in 6.5% of 724 first-degree relatives of 256 BAV patients, consistent with significant heritability although valve morphology was not concordant within families. In addition, 9.6% of relatives with a trileaflet valve were found to have aortic dilation, defined as 1.96 SD greater than expected for age, body size and sex (figure 1).…”
mentioning
confidence: 87%
“…There are still important limitations of this study to keep in mind 6. First, this study has inherent selection bias due to cross-sectional design.…”
mentioning
confidence: 97%
“…In their Heart  paper, Galian-Gay and colleagues report interesting data on familial BAV6: they have compiled data from a multicentre BAV registry on familial clustering and prevalence of BAV in FDR, on the impact of BAV morphological types and associated aortic dilation on the inheritance pattern. This study is the largest series of BAV families, including 256 BAV probands and 724 FDR.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Proposed screening algorithm in MVP first-degree relatives (FDR). TTE: transthoracic echocardiography; VT: ventricular tachycardia; SCD: sudden cardiac death <65 years of age 1. Connective tissue diseases and other syndromes (Le Thourneau et al13 provide an overview) 2.…”
mentioning
confidence: 99%